1996
DOI: 10.1111/j.1365-2559.1996.tb01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusocellular gonadal stromal tumour of the testis with epithelial and myoid differentiation

Abstract: We describe an unusual fusocellular gonadal stromal tumour with a benign behaviour in the left testis from a 16-year-old man. The neoplasm consisted of a non-encapsulated proliferation of irregularly arranged, fusiform cell bundles in fibrous connective tissue. The tumour cells contained a slightly infolded nucleus, some dilated rough endoplasmic reticulum cisternae, abundant filament bundles which connected to subplasmalemmal electron-dense bodies, pinocytotic vesicles and a discontinuous basal lamina. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…We diagnose this tumor as a myoid gonadal stromal tumor in keeping with the initial 1991 report [7]. In our review of the medical literature, we found 6 similar cases [4][5][6][7][8][9]. These tumors appeared to represent a distinct entity by displaying a distinct pattern of PTMC-like differentiation as characterized by electron microscopy and/or immunohistochemistry.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…We diagnose this tumor as a myoid gonadal stromal tumor in keeping with the initial 1991 report [7]. In our review of the medical literature, we found 6 similar cases [4][5][6][7][8][9]. These tumors appeared to represent a distinct entity by displaying a distinct pattern of PTMC-like differentiation as characterized by electron microscopy and/or immunohistochemistry.…”
Section: Discussionmentioning
confidence: 74%
“…This pattern closely mimicked the phenotype of PTMCs; thus, we believed that this was a myoid gonadal stromal tumor. As summarized in Table 2, an additional 6 similar tumors have been reported-that is, the reported tumors all displayed unequivocal myogenous features by various studies and were circumscribed, intratesticular masses that followed a benign clinical course [4][5][6][7][8]. Specifically, these tumors contained myofilaments by electron microscopy and/or had clear-cut immunoreactivity for 1 or more smooth muscle markers, including desmin, SMA, MSA, or SMM.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Pinieux et al noted the presence of a small number of sex cord elements in two cases of TF using CD99/MIC2 (Sertoli and Leydig cells) and anti-inhibin (Sertoli, and Leydig granulosa cells) (7). Nistal et al pointed out that the TF in their case was negative for keratin, S-100 protein and factor XIIIa, and therefor suggests that this tumor stems from peritubular myoid cells (10). The differential diagnosis includes: leiomyoma, neurofibroma, solitary fibrous tumor, and fibrosarcoma.…”
Section: Discussionmentioning
confidence: 97%
“…Intratesticular fibrous tumors are even more uncommon 1 . In previously published reports they were described under different names such as diffuse stromal form of gonadal stromal tumor, 2 thecoma like sertoli cell tumor, 3 testicular fibroma, 4 theca cell tumor, 5 myoid gonadal stromal tumor with epithelioid differentiation, 6 to name but a few. According to the recent WHO classification they are considered as sex cord/gonadal stromal tumors and classified under the tumors of thecoma/fibroma group 7 .…”
Section: Introductionmentioning
confidence: 99%